Identifying and managing the dimensions of relationship marketing for the foodservice industry / Assoc. Prof. Dr. Firdaus Abdullah and Agnes Kanyan - Abdullah, Firdaus; Agnes Kanyan (Research Management Institute (RMI), 2012)
As competition is becoming more intense, customers are increasingly demanding and price sensitive. Thus, building strong relationships with customers to gain competitive advantage and customer loyalty is crucial for survival and success in today's business environment. Although the relationship marketing discipline is relatively well researched, measuring instruments are limited and practically nonexistent in the foodservice industry. Therefore, this study proposes a new measuring instrument of relationship marketing which is uniquely designed for the foodservice industry. In particular, the underlying dimensions of relationship marketing as perceived by customers are identified and a framework for the enhancement of relationship marketing is developed. The study is expected to provide useful information to the foodservice industry in managing more effective relationship marketing programmes. The proposed 31 -item instrument has been empirically tested for unidimensionality, reliability and validity using both exploratory and confirmatory factor analysis. A factorial analysis suggests that relationship marketing is a multidimensional construct consisting of four key dimensions namely Communication, Trust, Empathy and Commitment. Communication emphasises the necessity to communicate in understanding manner, giving clear explanations and providing helpful advice. Trust refers to the ability to inspire confidence and to make reliable promises, whereas Empathy stresses the importance of exhibiting sympathy and reassurance, giving individual attention and understanding customer's specific needs. Lastly, Commitment describes the desire to provide excellent service and build long-term customer relationships. A subsequent multiple regression analysis reveals that the dimensions of relationship marketing were positively correlated with customer loyalty and Trust is found to be the most important dimension within the foodservice industry.